2014
DOI: 10.1136/jnnp-2014-308021
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spinal cord volume loss is related to clinical disability progression in multiple sclerosis

Abstract: SC MRI parameters including baseline UCCA and SC lesions were significant MRI predictors of disease progression. Progressive 24-month upper SC atrophy occurred in all MS subtypes, and was faster in patients exhibiting disease progression at month-24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
129
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 40 publications
15
129
1
2
Order By: Relevance
“…4 MRI measurement of cervical cord atrophy in patients with this disease provides valuable additional information related to disability that cannot be obtained from brain metrics. 5 A progressive reduction of the cervical cord cross-sectional area (CSA) occurs in PPMS, [6][7][8][9] and spinal cord atrophy has been shown to correlate with the severity of clinical disability. [10][11][12] Moreover, some cross-sectional studies have reported that spinal cord atrophy is an independent predictor of disability progression.…”
Section: Introductionmentioning
confidence: 99%
“…4 MRI measurement of cervical cord atrophy in patients with this disease provides valuable additional information related to disability that cannot be obtained from brain metrics. 5 A progressive reduction of the cervical cord cross-sectional area (CSA) occurs in PPMS, [6][7][8][9] and spinal cord atrophy has been shown to correlate with the severity of clinical disability. [10][11][12] Moreover, some cross-sectional studies have reported that spinal cord atrophy is an independent predictor of disability progression.…”
Section: Introductionmentioning
confidence: 99%
“…3 These current findings are in line with previous studies showing that cervical cord atrophy is more pronounced in progressive subtypes. 2,4 Some previous studies have used head images to measure cervical cord atrophy, 2,5,8,9 and a viable method is measuring the MUCCA. However, for MUCCA measurements to be widely applied to head images, in particular in a clinical trial setting, validation in a multicenter setting is necessary.…”
Section: 45mentioning
confidence: 99%
“…3,4 The MUCCA also has been measured recently on 3D T1-weighted MR images of the head covering the upper cervical cord, which has yielded promising results showing associations between MUCCA and clinical disability and disease progression. 2,5 Measuring the MUCCA from head MR images offers the opportunity to analyze MUCCA retrospectively in datasets without dedicated cervical 3D T1-weighted images, and it can reduce costs and patient burden in prospective studies by eliminating the need for separate cervical cord image acquisitions if these are only acquired to measure the MUCCA. An MR imaging contrast agent is commonly used to detect the bloodbrain barrier breakdown and inflammation in new lesions 12,13 in patients with MS, which might influence the MUCCA measurements by tissue-contrast changes.…”
mentioning
confidence: 99%
See 2 more Smart Citations